In envy country stories - Frank, Joan, 1949-; ebrary, Inc. (Notre Dame, Ind. : University of Notre Dame Press, 2010)
"Set in Paris, California, Italy, and Spain, Joan Frank's second story collection explores the uncertainties and triumphs of women and men in and out of love and marriage at varying ages and stages of contemporary American Life"--Cover p.[4].
A note on the type -- A thing that happens -- Betting on men -- Rearview -- In envy country -- Picaro -- Sandy candy -- Savoir faire, savoir vivre -- The sun on the Ganges.
Electronic reproduction.
Keywords: Man-woman relationships -- Fiction; Electronic books